2014
DOI: 10.1308/003588414x13946184903487
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of hyperbaric oxygen and sprayed keratinocyte suspension to tackle a difficult wound

Abstract: This is the first reported case in the literature to combine the use of a well established therapy to achieve wound healing (ie hyperbaric oxygen treatment) and a novel sprayed keratinocyte suspension technique to treat a challenging wound successfully. The merits and potential issues associated with these treatments are outlined and the case is detailed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Applications of autologous skin cell suspension (ASCS) have long been used in burn care for purposes of epidermal regeneration in deep partial‐thickness and full‐thickness injuries . More recently, ASCS has been used to benefit patients who have ulcers of various aetiologies, including VLUs and diabetic foot ulcers . Authors have observed that use of ASCS appears to restart the healing process and have hypothesized that the introduction of a population of healthy, disaggregated cells may modulate the wound environment and provide a source of healthy cells to stimulate healing of a wound that has been static for months.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Applications of autologous skin cell suspension (ASCS) have long been used in burn care for purposes of epidermal regeneration in deep partial‐thickness and full‐thickness injuries . More recently, ASCS has been used to benefit patients who have ulcers of various aetiologies, including VLUs and diabetic foot ulcers . Authors have observed that use of ASCS appears to restart the healing process and have hypothesized that the introduction of a population of healthy, disaggregated cells may modulate the wound environment and provide a source of healthy cells to stimulate healing of a wound that has been static for months.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians evaluating the use of ASCS in their treatment algorithms for chronic wounds have demonstrated favourable results; however, a prospective randomised study evaluating the use of the cell suspension in VLUs compared with standard compression therapy has not been conducted to date. Therefore, the objective of this pilot study was to evaluate the effectiveness of the addition of ASCS to standard compression therapy in comparison with compression therapy alone.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been demonstrated that skin grafting and bilayer artificial skin may also improve the rate of healing of DFUs 14,15 . Studies evaluating the use of autologous skin cell suspension (ASCS) as prepared using an Autologous Cell Harvesting Device (ACHD) as part of the treatment algorithm for chronic wounds have demonstrated favorable results 16‐20 . In a randomized clinical trial in which ASCS was combined with skin grafting for treatment of a mixture of different types of chronic wounds, there was a significant improvement in healing rate (14 days with ASCS vs 20 days without), reduced tendency for wound recurrence, and fewer complications compared to skin grafting alone 18 .…”
Section: Introductionmentioning
confidence: 99%